TINGKAT KETERAMPILAN TEKNIK DASAR BOLA VOLI SISWA EKSTRAKURIKULER SMP NEGERI 2 CERENTI - Mulyadi, Hidiatma; Agust, Kristi; Prima Aspa, Agus; Vai, Aref; Angga Lardika, Rola; Hilmi Wahdi, Agung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the level of basic volleyball technical skills of extracurricular students at SMP Negeri 2 Cerenti. This research used a quantitative descriptive method with a survey approach and measurement test techniques. The population in this study consisted of all male students participating in the volleyball extracurricular program at SMP Negeri 2 Cerenti, totaling 10 students. The sampling technique used was total sampling, so the entire population was selected as the research sample. The instrument used was a basic volleyball skills test covering underhand passing, overhead passing, underhand service, overhand service, and smash skills based on the instrument developed by Widiastuti. Data analysis techniques employed descriptive statistics in the form of averages and percentages.The results showed that the level of basic volleyball technical skills of the extracurricular students at SMP Negeri 2 Cerenti was categorized as good for 4 students (40%), fair for 3 students (30%), poor for 2 students (20%), and very poor for 1 student (10%). The overall average score of basic volleyball technical skills was 117.40. Based on these findings, it can be concluded that the level of basic volleyball technical skills of extracurricular students at SMP Negeri 2 Cerenti falls into the good category.